Evaluation of the musculoskeletal system of patients in cardiopulmonary and metabolic rehabilitation programs Avaliação do sistema locomotor de pacientes de programas de reabilitação cardiopulmonar e metabólica - De Carvalho T.* (2010)
Background: Participants of cardiopulmonary and metabolic rehabilitation (CPMR) programs may present with musculoskeletal changes that may affect treatment compliance and effectiveness. Objective: To develop an instrument for evaluation of the musculoskeletal system and identification of problems, especially those related to exercise, so that patients can be cleared to exercise with no restrictions, cleared with restrictions, or not cleared before approval from a specialist. Methods: Construction and validation (according to Cronbach's alpha) of a musculoskeletal system assessment inventory (MSSAI), for subsequent administration to participants in CPMR programs. Results: A total of 103 individuals participating in CPMR programs were evaluated by means of the MSSAI, whose internal validity and reliability proved to be satisfactory. Of these, 33 were men (32%) and 70 were women (68%), with age ranging from 36 to 84 years; 47 (45.6%) had already been diagnosed with musculoskeletal system disorders; 39 (37.9%) had already received specific treatment for the musculoskeletal system; 33 (32%) used to take medications to relieve symptoms related to the musculoskeletal system; and 10 (9.7%) had a medical restriction for performing some type of exercise. We should point out that 48 individuals (46.6%) reported pain in the musculoskeletal system; in 14 (13.6%) of them, the pain worsened by exercise, and this should have prevented them from participating in exercise programs before receiving approval from a specialist. Conclusion: The MSSAI, whose internal validity and reliability proved satisfactory, showed that there was some restriction to exercise practice for almost half of the individuals participating in CPMR programs, and that some of them should not have been cleared without approval from a specialist.